Damage Associated Molecular Pattern Molecule-Induced microRNAs (DAMPmiRs) in Human Peripheral Blood Mononuclear Cells - Unlu, Sebnem; Tang, Siuwah; Wang, E. na; Martinez, Ivan; Tang, Daolin; Bianchi, Marco E.; Zeh, III, Herbert J.; Lotze, Michael T. (PLOS ONE, 2012)
Endogenous damage associated molecular pattern molecules (DAMPs) released from necrotic, damaged or stressed cells are associated with an inflammatory response. Whether the microRNA (miR) expression signature of this response is different from that of a pathogen associated molecular pattern (PAMP)-stimulated inflammatory response is unknown. We report here that miR-34c and miR-214 are significantly expressed in fresh human peripheral blood mononuclear cells (PBMCs) exposed to DAMP-containing freeze-thaw lysates, or to conditioned media from serum-starved and glucose-deprived cells (p<6×10−4 and p<3.7×10−3), respectively. Interestingly, only miR-34c expression was differentially expressed in PBMCs exposed to freeze-thaw lysates or conditioned media from wildtype High Mobility Group B1 (HMGB1+/+) mouse embryonic fibroblast (MEF) cells, when compared to cultures exposed to lysates or conditioned media from HMGB1−/− MEFs. miR-155 expression in these cultures was negligible, but was significantly expressed in PBMCs stimulated with Lipopolysaccahride (LPS) or most other Toll-like receptor (TLR) ligands, making it the prototypic “PAMPmiR”. Exposure to a damaged human colorectal carcinoma cell line lysate (HCT116) similarly resulted in increased miR-34c and miR-214 levels. When PBMCs were pre-transfected with anti-miR-34c and then exposed to lysate, expression levels of IKKγ mRNA, a putative target of miR-34c, increased, while protein levels of IKKγ in cultures transfected with a pre-miR-34c were abrogated. Levels of miR-34c expression (as well as pro-inflammatory cytokines, IL-1β and TNFα) decreased when PBMC cultures were briefly pre-incubated with the K+ channel (inflammasome) inhibitor, glybenclamide, suggesting that inflammasome activation is upstream of miR-34c expression in response to DAMPs. Our findings demonstrate that a specific microRNA expression signature is associated with the inflammatory response to damaged/injured cells and carries implications for many acute and chronic inflammatory disorders.